A novel low‐bandgap conjugated polymer based on Ru(II) bis(acetylide) complex and BODIPY moieties. Issue 12 (1st April 2014) - Zhang, Shuwei; Sheng, Yuan; Wei, Guo; Quan, Yiwu; Cheng, Yixiang; Zhu, Chengjian
ABSTRACT A novel conjugated polymer P‐1 incorporating Ru(II) bis(acetylide) complex and borondipyrromethene (BODIPY) moieties in the main chain was synthesized by Pd‐catalyzed Sonogashira coupling reaction of diethynyl substituted BODIPY derivative (M‐1) and Ru(II) bis(acetylide) complex (M‐2), and the reference polymer P‐2 was obtained from the same method as preparation of P‐1. Compared with P‐2, Ru(II)‐containing polymer P‐1 shows low‐bandgap as 0.87 eV from cyclic voltammetry, and obvious redshifts in both UV–vis absorption and fluorescence spectra. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1686–1692